2022
DOI: 10.31235/osf.io/9q7xj
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Did the pandemic increase social media-induced appearance pressures? A longitudinal analysis of social media caused appearance-related pressures before and during the Covid-19 pandemic

Abstract: Has the use of social media intensified and increased appearance-related pressures during the Covid-19 pandemic? A growing body of research has suggested that body image concerns and disordered eating have increased during the Covid-19 pandemic. One of the potential pathways includes an increase in social media use. However, examinations of this pathway have been limited because of the lack of longitudinal data. Drawing on a four-wave population-based survey, we demonstrate that social media-based appearance p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…People's perceptions of their bodies can be distorted by constant exposure to digitally altered images, which can lead to dissatisfaction and an urge to conform to unrealistic beauty standards (F & J, 2005). Furthermore, a 2020 study that was written in the Body Image journal found that using photo-based social media platforms is associated with a higher likelihood of engaging in appearance-centred behaviours, like comparing one's body to others and seeing oneself as an object (Sarpila, Koivuka, & Aberg, 2022) .…”
Section: Factors Promoting Negative Body Image In Youthmentioning
confidence: 99%
“…People's perceptions of their bodies can be distorted by constant exposure to digitally altered images, which can lead to dissatisfaction and an urge to conform to unrealistic beauty standards (F & J, 2005). Furthermore, a 2020 study that was written in the Body Image journal found that using photo-based social media platforms is associated with a higher likelihood of engaging in appearance-centred behaviours, like comparing one's body to others and seeing oneself as an object (Sarpila, Koivuka, & Aberg, 2022) .…”
Section: Factors Promoting Negative Body Image In Youthmentioning
confidence: 99%